Input and Output as Reflected in Postgraduate Translation-Oriented Training. An ESP-Centred Approach - Maria Cristina MIUȚESCU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
In quest of enhancing consistent performance across all the skills encompassed by a proficient translator’s loadout, the curricula of bachelor and master’s degrees are oftentimes subject to thorough scrutinization. In this respect, special consideration is usually given to the development of the textual and transfer sub-competences whose technical and practical mastery eventually determines the quality of the message rendered into the target language. Based on this premise, the study provides a brief overview of the peculiarities displayed by these two sub-competences as reflected in the questions addressed to a group of MA students pursuing a degree in Translation Studies (TS) and to the academic staff in charge of instructing them.